Nearly efficient likelihood ratio tests for seasonal unit roots - Michael Jansson; Morten Ørregaard Nielsen (Queen's University, Department of Economics, 2009)
In an important generalization of zero frequency autoregressive unit root tests, Hylleberg, Engle, Granger, and Yoo (1990) developed regression-based tests for unit roots at the seasonal frequencies in quarterly time series. We develop likelihood ratio tests for seasonal unit roots and show that these tests are nearly efficient in the sense of Elliott, Rothenberg, and Stock (1996), i.e. that their local asymptotic power functions are indistinguishable from the Gaussian power envelope. Currently available nearly efficient testing procedures for seasonal unit roots are regression-based and require the choice of a GLS detrending parameter, which our likelihood ratio tests do not.
Keywords: C12; C22; 330; Likelihood Ratio Test; Seasonal Unit Root Hypothesis; Unit Root Test; Maximum-Likelihood-Methode; Stochastischer Prozess